The role of DPO-1 and XE991-sensitive potassium channels in perivascular adipose tissue-mediated regulation of vascular tone - Tsvetkov, Dmitry; Schubert, Rudolf (Frontiers in physiology, 2016)
The anti-contractile effect of perivascular adipose tissue (PVAT) is an important mechanism in the modulation of vascular tone in peripheral arteries. Recent evidence has implicated the XE991-sensitive voltage-gated Kv (KCNQ) channels in the regulation of arterial tone by PVAT. However, until now the in vivo pharmacology of the involved vascular Kv channels with regard to XE991 remains undetermined, since XE991 effects may involve Ca2+ activated BKCa channels and/or voltage-dependent Kv1.5 channels sensitive to diphenyl phosphine oxide-1 (DPO-1). In this study, we tested whether Kv1.5 channels are involved in the control of mesenteric arterial tone and its regulation by PVAT. Our study was also aimed at extending our current knowledge on the in situ vascular pharmacology of DPO-1 and XE991 regarding Kv1.5 and BKCa channels, in helping to identify the nature of K+ channels that could contribute to PVAT-mediated relaxation. XE991 at 30 µM reduced the anti-contractile response of PVAT, but had no effects on vasocontraction induced by phenylephrine (PE) in the absence of PVAT. Similar effects were observed for XE991 at 0.3 µM, which is known to almost completely inhibit mesenteric artery VSMC Kv currents. 30 µM XE991 did not affect BKCa currents in VSMCs. Kcna5-/- arteries and wild-type arteries incubated with 1 µM DPO-1 showed normal vasocontractions in response to PE in the presence and absence of PVAT. Kv current density and inhibition by 30 µM XE991 were normal in mesenteric artery VSMCs isolated from Kcna5-/- mice. We conclude that Kv channels are involved in the control of arterial vascular tone by PVAT. These channels are present in VSMCs and very potently inhibited by the KCNQ channel blocker XE991. BKCa channels and/or DPO-1 sensitive Kv1.5 channels in VSMCs are not the downstream mediators of the XE991 effects on PVAT-dependent arterial vasorelaxation. Further studies will need to be undertaken to examine the role of other Kv channels in the phenomenon.
Gesehen am 15.08.2019